2016
DOI: 10.5817/cp2016-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Anonymously male: Social media avatar icons are implicitly male and resistant to change

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Hegarty and Pratto (2001) found that participants' tendency to focus on gay men more than straight men to explain differences was reduced when participants believed that gay men represented the majority of the research sample. In contrast, recent studies on gender and race-based frequency manipulations were ineffective in reducing participants' tendency to use men to represent humanity (Bailey & LaFrance, 2016a) and to think of Whiteness as being unmarked (Hegarty, 2017). Yet, these studies were limited in duration, and longer lasting interventions might have a greater impact.…”
Section: Frequency Of Instantiationmentioning
confidence: 91%
See 4 more Smart Citations
“…Hegarty and Pratto (2001) found that participants' tendency to focus on gay men more than straight men to explain differences was reduced when participants believed that gay men represented the majority of the research sample. In contrast, recent studies on gender and race-based frequency manipulations were ineffective in reducing participants' tendency to use men to represent humanity (Bailey & LaFrance, 2016a) and to think of Whiteness as being unmarked (Hegarty, 2017). Yet, these studies were limited in duration, and longer lasting interventions might have a greater impact.…”
Section: Frequency Of Instantiationmentioning
confidence: 91%
“…This work parallels research that asks participants to list examples of different categories (e.g., Battig & Montague, 1969). People are more likely to describe a person, a voter, a famous person, an American, and a gender unspecified book character as male than as female (Bailey & LaFrance, 2016a; DeLoache, Cassidy, & Carpenter, 1987; Gastil, 1990; M. C. Hamilton, 1991; Merritt & Kok, 1995; Miller, Taylor, & Buck, 1991; Moyer, 1997; van Berkel, Molina, & Mukherjee, 2017).…”
Section: Role Of Categorizationmentioning
confidence: 99%
See 3 more Smart Citations